Formulasi Sediaan Acne Patch Ekstrak Etanol Daun Coleus scutellarioides L. terhadap Propionibacterium acnes dan Staphylococcus epidermidis - Abdul Wahid Suleman; Natasya Virginia; Nasrawati Basir; Sriyanty Sadsyam; Chikita Inaku; Nurfiddin Farid (Sultan Agung Islamic University, 2026)
Background: The increasing prevalence of acne vulgaris and the growing resistance of Propionibacterium acnes and Staphylococcus epidermidis to conventional antibiotics have encouraged the development of safer and more effective natural therapies. This study aimed to formulate and evaluate the physical stability of an acne patch containing ethanolic extract of miana leaves (Coleus scutellarioides L.) and to determine its antibacterial activity against P. acnes and S. epidermidis. Methods: Miana leaves were extracted by maceration using 96% ethanol and formulated into acne patches at concentrations of 0.5%, 1%, and 2% using hydroxypropyl methylcellulose (HPMC) as the film-forming polymer. The formulations were evaluated for organoleptic properties, weight uniformity, pH, thickness, moisture content, and stability through a cycling test. Antibacterial activity was assessed in vitro using the agar diffusion method. Results: All formulations exhibited acceptable physical characteristics and remained stable throughout the cycling test. Statistical analysis revealed significant differences in antibacterial activity among the formulations (p < 0.05). The inhibition zones increased proportionally with extract concentration, indicating a concentration-dependent antibacterial effect. The formulation containing 2% miana leaf extract demonstrated the highest antibacterial activity against both P. acnes and S. epidermidis and showed significantly greater inhibition than the lower concentrations (p < 0.05). Furthermore, this formulation maintained satisfactory physical stability and quality parameters. Conclusion: These findings indicate that the 2% miana leaf extract acne patch is the optimal formulation and has potential as a safe, stable, and effective natural anti-acne product.